SIKAP DAN PERILAKU SISWA PADA PENYELENGGARAAN UPACARA BENDERA DAN PENGARUHNYA TERHADAP RASA NASIONALISME - Siti Aulia Dewi Amir; Adeng Wijaya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The lack of a sense of nationalism of students in organizing the Flag Ceremony is motivated by the attitudes and behavior of students that are not in accordance with the reference to the rules for carrying out the flag ceremony. The formulation of the problem of this research is how the attitudes and behavior of students in organizing the flag ceremony and how it affects the sense of nationalism of class XI students of SMA Negeri 1 Guguak District. The hypothesis of this research is that there is a significant relationship between students' attitudes and behavior with students' sense of nationalism at the flag ceremony for class XI SMA Negeri 1 Guguak District in the 2013/2014 academic year, at a significant level of 0.05 (95%). This type of research is correlational research with a quantitative approach. The population in this study were students of class XI SMA Negeri 1 Guguak District. The total population is 320 students and the sample used is 67 with proportional random sampling technique. Data collection was carried out using questionnaires and observation methods. The results of this study indicate that (1) The average attitude and behavior of students in organizing the flag ceremony for class XI SMA Negeri 1 Guguak District in the 2013/2014 academic year is in the very low category. This can be seen from the average value (mean) of attitudes and behavior, namely 42.41 which is in the interval of 30 - 60; (2) The students' average sense of nationalism during the flag ceremony for class XI SMA Negeri 1 Guguak District in the 2013/2014 academic year was in the medium category. This can be seen from the average value (mean) of a sense of nationalism, namely 77.94 which is in the interval 72 – 79; (3) There is a significant relationship between attitudes and behavior with a sense of nationalism in class XI SMA Negeri 1 Guguak District 2013/2014 academic year. 2) = 65 at a significance of 0.05 and the magnitude of the correlation coefficient is 0.446. The magnitude of the coefficient of determination (R2) is 0.198. This means that the contribution of students' attitudes and behavior in organizing the flag ceremony to the sense of nationalism in class XI at SMA Negeri 1 Guguak District is 19.8%.Keywords: Attitude, Student Behavior, Nationalism.